Comparison of Intracranial Hemorrhage and Clinical Outcomes Among Patients Undergoing Mechanical Thrombectomy with and without Thrombolytic Therapy - Zulfikar Memis; Irem Kuru (Haseki Tıp Bülteni)
Aim: It remains controversial whether intravenous tissue plasminogen activator (IV tPA) increases complications in patients undergoing mechanical thrombolysis. In this study, we aimed to show the effect of IV tPA administration on complications. Methods: In this cross-sectional study, the records of patients who were followed up at the stroke center and underwent mechanical thrombectomy (MT) between 2022 and 2023 were retrospectively reviewed. Demographic data, cerebral angiography data, neuroimaging time, medical history, and medication use; neurologic examination findings at baseline, 24th hour, and 3rd month were obtained from the patient files. Patients were divided into two groups according to whether intracranial tPA was administered before MT and two groups according to the presence of intracranial hemorrhage at 24 hours. Results: A total of 172 patients [94 women (54.7%) and 78 men (45.3%)] were included in the study. Mean age was 67.6±14.7 years. At 24 h, the rate of symptomatic intracranial hemorrhage (sICH) was significantly (p=0.004) higher in the thrombectomy group than in the tPA plus thrombectomy group. The admission (p=0.033) and 24-hour National Institutes of Health Stroke Scale (p=0.001) scores were significantly higher in the sICH group than in the non-sICH group. Third-month modified Rankin scale score (p=0.003), diastolic embolism rate (p=0.009), and Tan score (p=0.007) were significantly higher in the sICH group than in the non-sICH group. Conclusion: Intravenous tissue plasminogen activator did not increase sICH or distal embolism in patients undergoing MT, and there was no difference in terms of favorable clinical outcomes. Symptomatic intracranial hemorrhage was associated with increased mortality and poor clinical outcome.